2016
DOI: 10.1155/2016/1038950
|View full text |Cite
|
Sign up to set email alerts
|

Review on Vertical Twin-Roll Strip Casting: A Key Technology for Quality Strips

Abstract: Nowadays near-net-shape casting technology is an important area of research in the iron and steel industry. Among different kinds of near-net-shape casting process, twin-roll casting process has received much attention among researchers. Twin-roll casting (TRC) has been the subject of extensive research, not only to develop the technology but also to achieve an understanding of microstructural evolution and to produce quality strips. The main issues concerning the design and operation of twin-roll casters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Induction heating induces eddy currents within conductors. Eddy currents create heating effects to melt the metal [6] while strip casting process is a near-net-shape casting technology, for the production of thin strips having thickness of about 0.1 mm to 6.0 mm. This process produces thin strips directly from the liquid metal by combining casting and rolling in a single step solidifying the liquid metal when it comes in contact with the rotating mold [7].…”
Section: Methodsmentioning
confidence: 99%
“…Induction heating induces eddy currents within conductors. Eddy currents create heating effects to melt the metal [6] while strip casting process is a near-net-shape casting technology, for the production of thin strips having thickness of about 0.1 mm to 6.0 mm. This process produces thin strips directly from the liquid metal by combining casting and rolling in a single step solidifying the liquid metal when it comes in contact with the rotating mold [7].…”
Section: Methodsmentioning
confidence: 99%
“…In the same manner as it has been realized in works [13][14][15][16][17][18] , the modeling has been provided by means of the FE software package ANSYS. Besides the already mentioned publications, this software has also been successfully used to simulate twin-roll casting of strips of aluminum and aluminum alloys 20 , various steels [21][22] and magnesium alloys 23 .…”
Section: Numerical Modeling Of the New Twin-roll Casting Methodsmentioning
confidence: 99%
“…Sahoo et al described and investigated the effect of casting rate and melt superheat in the twin-roll casting of an Al-33Cu alloy on conditions of the strip formation using the same software 14 . It has been shown that increasing of these parameters reduces the deformation zone length, because the time needed for solidification of the strip becomes longer.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the much thinner typical sheet and extrusion profiles that are finally used in products, this requires thickness reductions in excess of 90%, which explains the high deformation and reheating energy that is used in this field. Therefore, this section places focus on promising energy-reduced downstream processing methods in that context. …”
Section: Better Sustainability Through Improved Large-scale Processingmentioning
confidence: 99%